Development and Testing of Asbestos Free Brake Pad Material - Vijay, R.; Rajesh Kumar, S.; Satish, V.; Thiyagarajan, V. (Asian Review of Mechanical Engineering, 2012)
An attempt is made through this project to incorpate 20% alumina fiber in automotive brake pad friction composites. Ingredients such as glass fiber, steel wool, rock wool, phenolic resin, barite, graphite, chalk powder and friction dust are added with alumina fiber to make up the composition. The developed brake pad composites have exhibited consistent coefficients of friction in the range of 0.3-0.4 and wear resistances are 1.2 times greater than asbestos frictional materials.